5,10-methylenetetrahydrofolate reductase C677T gene polymorphism as a risk factor for premature coronary artery disease in patients with type 2 diabetes mellitus - Mohammed, Nisreen O.; Ali, Ibtisam A.; Elamin, Bahaelddin K.; Saeed, Bakri Osman (Frontiers in Endocrinology, 2025)
BackgroundAfrica, like the rest of the world, is experiencing an increasing prevalence of diabetes mellitus. Diabetes increases the risk for coronary artery disease (CAD) by fourfold compared to people without diabetes. C677T polymorphism in methylenetetrahydrofolate reductase (MTHFR) and hyperhomocysteinemia were reported by many studies as risk factors for CAD among patients with type 2 diabetes mellitus (T2DM). Early detection of modifiable risk factors for CAD is an important aspect of management of diabetes. This is the only study in Sudan which investigates the association between MTHFR genotypes and plasma homocysteine levels, and their role in premature CAD (PCAD) among patients with T2DM.MethodsThis study is a comparative study. We enrolled 226 Sudanese patients with T2DM, age range 25-60 years, recruited from Alshaab and Omdurman teaching hospitals in Khartoum State. 113 patients had CAD confirmed by angiography and electrocardiography (ECG) and 113 had no evidence of CAD. Polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP), using Hinf1 restriction enzyme, were used to determine MTHFR genotypes. Plasma homocysteine levels were determined by enzymatic assay on the Hitachi Cobas Integra® 400 plus. Data was analyzed using statistical package for Social Sciences (SPSS) 23, using Mann-Whtney U test, general linear model, Chi-square test and logistic regression analysis.ResultsThe frequencies of TT, CT, and CC genotypes were 16,40 and 44% among T2DM patients with PCAD. In T2DM patients without PCAD, the frequencies of TT, CT, and CC genotypes were 00,19 and 83%. The T allele showed strong association with PCAD among T2DM patients, p <0.001, odds ratio (OR) 6.2, 95% CI (3.4-11.6). Patients with PCAD showed higher plasma homocysteine levels than patients without PCAD (13.5 µmol/L versus 10 µmol/L, p < 0.001). The T allele had significant effect on homocysteine level, (p <0.001). Plasma homocysteine levels were higher in individuals with TT genotype than those with CT or CC genotypes in patients with PCAD (16.2 + 5.3, 14.3 + 5.7 and 12.9 + 5.02 µmol/L, p=0.017). Homocysteine levels showed a significant association with CAD, p<0.001, OR 3.2, 95% CI (1.9—5.5).ConclusionsOur study suggests that C677T polymorphism of MTHFR gene and hyperhomocysteinemia are risk factors for PCAD in Sudanese population with T2DM.